2019
DOI: 10.3349/ymj.2019.60.12.1164
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Nutritional Status Score is Associated with All-Cause Mortality in Patients with Antineutrophil Cytoplasmic Antibody-Associated Vasculitis

Abstract: PurposeThe controlling nutritional status (CONUT) score was developed to detect undernutrition in patients. Here, we investigated whether the CONUT score estimated at diagnosis could help predict poor outcomes [all-cause mortality, relapse, and end-stage renal disease (ESRD)] of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV).Materials and MethodsWe retrospectively reviewed and collated data, including baseline characteristics, clinical manifestations (to calculate AAV-specific indices),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
9
1
Order By: Relevance
“…2,6,9,11,12,14 However, compared to the patients included in other studies, our patients were younger, and only 10 patients were over 65 years old, indicating that age was not a risk factor. Furthermore, consistent with the findings of previous studies, 2,6,8,9,11,12,15 our results showed that high serum creatinine level was a risk factor for mortality. The cut-off value for creatinine was found to be >2.1 mg/dL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2,6,9,11,12,14 However, compared to the patients included in other studies, our patients were younger, and only 10 patients were over 65 years old, indicating that age was not a risk factor. Furthermore, consistent with the findings of previous studies, 2,6,8,9,11,12,15 our results showed that high serum creatinine level was a risk factor for mortality. The cut-off value for creatinine was found to be >2.1 mg/dL.…”
Section: Discussionsupporting
confidence: 93%
“…9,11 Also, high BVAS was found to be an independent risk factor for mortality, consistent with our findings. 12 On the other hand, although an increased FFS value was reported to be a risk factor for mortality in previous studies, 6,8,15 the increase in FFS was not significant in our study (p=0.15).…”
Section: Survival Function Censoredcontrasting
confidence: 81%
See 1 more Smart Citation
“…30 Similarly, we demonstrated that a poor nutritional status was associated with a higher BVAS, and that it was a risk factor for ESRD occurrence. 31 One explanation for these findings is that underweight patients are at an increased risk of low muscle mass, 32,33 muscle mass is associated with chronic kidney disease. 34,35 The new BMI was proposed since the conventional BMI, which is defined as weight divided by height squared, has limitations in reflecting the three-dimensional human body.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…CONUT score at diagnosis was found to be associated with all-cause mortality during follow-up in AAV patients. 70 Systemic immune-inflammation index (SII) is a formula using three blood lineages as follows: SII=platelet count×neutrophil count/lymphocyte count. 71 In theory, the inflammatory burden of AAV may have the capability to increase the number of neutrophils and platelets, and decrease that of lymphocytes.…”
Section: Serological Indices In Korean Patients With Aavmentioning
confidence: 99%